Micro-scale analysis of liquid water breakthrough inside gas diffusion layer for PEMFC using X-ray computed tomography and Lattice Boltzmann Method - P. Satjaritanun (2018)
© The Author(s) 2017. The main objective of this work is to predict the breakthrough pressure of liquid water transport through the gas diffusion layer (GDL) and/or micro porous layer (MPL) used in polymer electrolyte membrane fuel cells. The integration of structural GDL and MPL with Lattice Boltzmann Method is primary focused. The numerical predictions are also compared with experimental data. The interaction between liquid phase and different surface treatments of solid structures controls the evolution of liquid water and the change of capillary pressure. The geometries of GDLs and MPLs were obtained by three dimensional reconstructed micro-structure images from both nanometer and micrometer-scaled high spatial resolution X-ray computed tomography (CT). The predictions of water breakthrough pressure agree with the data observed in the experiment. They also reveal that the breakthrough pressure and liquid water evolution inside the GDL samples are different when the wetting properties of GDL and/or MPL are changed. The detailed microporous property can be obtained using high spatial resolution image from nanometer-scaled X-ray CT, a.k.a. Nano X-ray CT. Meanwhile, images from micrometer-scaled X-ray CT, a.k.a. Micro X-ray CT, give proper field of view to cover complete vision of porous materials, including cracks in the MPL.